Automated item‐level measures of verbal fluency in semantic and logopenic primary progressive aphasia - Vonk, Jet M. J. (2025)
Introduction: Verbal fluency tasks are widely used in primary progressive aphasia (PPA), but most studies rely only on total correct responses, overlooking qualitative features of the words produced. We applied a scalable computational framework to extract item-level features from fluency responses in semantic (svPPA) and logopenic PPA (lvPPA) to test their value for differential diagnosis.Methods: We analyzed animal fluency responses from 113 participants (40 svPPA, 40 lvPPA, 33 controls) using an automated pipeline extracting nine psycholinguistic features. Group differences were examined with (co)variance models, classification with logistic regression, and brain-behavior associations via structural MRI.Results: All features except semantic variability distinguished svPPA from lvPPA. Models including features outperformed (AUC=.86) those using only total correct or clinical variables (AUC=.60-.68). Features related mainly to temporal lobe atrophy, whereas total correct also related to the angular gyrus.Discussion: Automated item-level analysis offers a sensitive, scalable method for supporting PPA diagnosis and monitoring.